Question
upstudy study bank question image url

EXERCISE 6 1. Evaluate, without using a calculator. (a) \( \cos 330^{\circ} \cdot \sin 60^{\circ} \) (c) \( \tan 315^{\circ}-2 \cos 60^{\circ}+\sin 210^{\circ} \) (e) \( \frac{\tan 330^{\circ}}{\sin 330^{\circ}} \) (g) \( \sin 150^{\circ}-\tan 240^{\circ} \cdot \cos 210^{\circ} \) (i) \( \frac{\tan 150^{\circ}}{\tan 240^{\circ}}-\frac{\sin 300^{\circ}}{\sin 120^{\circ}} \) (k) \( \frac{\tan 225^{\circ}-\sin x}{\sin x+\sin 270^{\circ}} \)

Ask by Clark Carlson. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) 3/4 (c) –5/2 (e) 2/√3 (g) 2 (i) 2/3 (k) –1

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Bonus Knowledge

Sure! Let's break it down and evaluate each expression step by step: **(a)** \( \cos 330^{\circ} \cdot \sin 60^{\circ} \) First, recall that \( \cos 330^{\circ} = \cos(-30^{\circ}) = \cos 30^{\circ} = \frac{\sqrt{3}}{2} \). For \( \sin 60^{\circ} \), we know that \( \sin 60^{\circ} = \frac{\sqrt{3}}{2} \). Thus, the expression becomes: \[ \cos 330^{\circ} \cdot \sin 60^{\circ} = \frac{\sqrt{3}}{2} \cdot \frac{\sqrt{3}}{2} = \frac{3}{4} \] --- **(c)** \( \tan 315^{\circ} - 2 \cos 60^{\circ} + \sin 210^{\circ} \) Here, \( \tan 315^{\circ} = -1 \) (since \( 315^{\circ} \) is in the fourth quadrant), \( \cos 60^{\circ} = \frac{1}{2} \) leads to \( 2 \cos 60^{\circ} = 1 \), and \( \sin 210^{\circ} = -\frac{1}{2} \). Therefore, we have: \[ \tan 315^{\circ} - 2 \cos 60^{\circ} + \sin 210^{\circ} = -1 - 1 - \frac{1}{2} = -2.5 \] --- **(e)** \( \frac{\tan 330^{\circ}}{\sin 330^{\circ}} \) First, \( \tan 330^{\circ} = -\frac{1}{\sqrt{3}} \) (because \( \tan 330^{\circ} = \tan(-30^{\circ}) \)), and \( \sin 330^{\circ} = -\frac{1}{2} \), hence: \[ \frac{\tan 330^{\circ}}{\sin 330^{\circ}} = \frac{-\frac{1}{\sqrt{3}}}{-\frac{1}{2}} = \frac{2}{\sqrt{3}} = \frac{2\sqrt{3}}{3} \] --- **(g)** \( \sin 150^{\circ} - \tan 240^{\circ} \cdot \cos 210^{\circ} \) Here \( \sin 150^{\circ} = \frac{1}{2} \), \( \tan 240^{\circ} = \frac{1}{\sqrt{3}} \), and \( \cos 210^{\circ} = -\frac{\sqrt{3}}{2} \). Plugging these in, we get: \[ \tan 240^{\circ} \cdot \cos 210^{\circ} = \frac{1}{\sqrt{3}} \cdot -\frac{\sqrt{3}}{2} = -\frac{1}{2} \] So: \[ \sin 150^{\circ} - \tan 240^{\circ} \cdot \cos 210^{\circ} = \frac{1}{2} - (-\frac{1}{2}) = 1 \] --- **(i)** \( \frac{\tan 150^{\circ}}{\tan 240^{\circ}} - \frac{\sin 300^{\circ}}{\sin 120^{\circ}} \) Calculating each part, we find \( \tan 150^{\circ} = -\frac{1}{\sqrt{3}} \) and \( \tan 240^{\circ} = \frac{1}{\sqrt{3}} \), giving us: \[ \frac{\tan 150^{\circ}}{\tan 240^{\circ}} = \frac{-\frac{1}{\sqrt{3}}}{\frac{1}{\sqrt{3}}} = -1 \] Also, \( \sin 300^{\circ} = -\frac{\sqrt{3}}{2} \) and \( \sin 120^{\circ} = \frac{\sqrt{3}}{2} \), so: \[ \frac{\sin 300^{\circ}}{\sin 120^{\circ}} = \frac{-\frac{\sqrt{3}}{2}}{\frac{\sqrt{3}}{2}} =

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy